Local Wisdom-Based Environmental Management Policy in Indonesia: Challenges and Implementation - Aldyan, Arsyad; Putri, Kartika Asmanda; Aldyan, Rizal Akbar; Alasttal, Abdelrahman (CV. Ius et Ambientis, 2024)
Local wisdom encompasses community-derived knowledge and practices transmitted through generations, highlighting the importance of balance with the environment. In Indonesia, traditional methods like the size in Papua and subak in Bali are crucial for maintaining ecological equilibrium. This study seeks to investigate the influence of local wisdom on environmental management and assess the degree to which Indonesian environmental policy facilitates or obstructs its application. This research employs a normative legal method and literature analysis to analyze laws, regulations, and customary practices about environmental governance. The findings indicate that although several legislative instruments—such as Law No. 32/2009 on Environmental Protection and Law No. 5/1990 on Conservation—recognize and endorse traditional knowledge, obstacles remain. Modernization, divergent commercial interests, and insufficient local government backing frequently marginalize Indigenous knowledge. Furthermore, the execution of policies is often inconsistent and occasionally detrimental. The study asserts that incorporating indigenous knowledge into environmental policy formulation is crucial for sustainable resource management in Indonesia. Enhancing legal acknowledgment, promoting multi-stakeholder cooperation, and increasing policymakers' awareness are essential. Acknowledging local knowledge guarantees ecological sustainability and promotes social fairness for indigenous populations